Factors Related to Stunting in the Working Area of Palla Community Health Center, Southwest Sumba Regency - Bosko Dapa Toda; Intje Picauly; Helga Ndun (Universitas Nusa Cendana, 2022)
Stunting is a health problem in Indonesia, with the prevalence of stunting in children under five reaching 30.8%. Stunting is a condition of failure of growth and development of children under five due to a lack of nutritional intake for a long time. Stunting is caused by the provision of food that is not following nutritional needs so that the child grows too short for his age. The purpose of this study was to determine the factors associated with the incidence of stunting in the working area of ​​the Palla Community Health Center, Southwest Sumba Regency. This type of research was an analytic survey with a case-control study design, carried out from December 2020-January 2021. The sample size in this study was divided into two, namely 48 case respondents and 48 control respondents. Data were analyzed using univariate and bivariate. The results showed that variables, namely parents' income level, mother's education level, mother's level of knowledge, history of infectious disease, and consumption pattern, were associated with stunting incidence (p-value<0.05) in the working area Palla Community Health Center. Therefore, an active role from families of children under five, especially mothers, and the role of health workers in stunting prevention efforts is necessary to curb stunting.